A pure church? Ecclesiological reflections from the Gospel of Matthew. (3rd July 2014) - France, Richard
Abstract : The distinctive nature of the rural church community is considered in relation to the question of 'belonging'. It is suggested that the Gospel of Matthew provides useful guidelines for understanding such a community. It displays on the one hand a clear sense of the ultimate division between saved and lost but on the other hand a reluctance to draw clear lines between insiders and outsiders as far as the earthly community is concerned. There will be surprises at the final judgment. Until then, wheat and weeds must grow together until harvest, even though pragmatic measures will be needed to maintain the church's witness. Such a church is an inclusive school of discipleship rather than an exclusive gathering of the saved.